Emerging Therapeutic Approaches to Combat COVID-19: Present Status and Future Perspectives - Vivekanandhan, Karthik; Shanmugam, Poornima; Barabadi, Hamed; Arumugam, Vigneshwaran; Daniel Raj Daniel Paul Raj, Dharun; Sivasubramanian, Manikandan; Ramasamy, Subbaiya; Anand, Krishnan; Boomi, Pandi; Chandrasekaran, Balakumar; Arokiyaraj, Selvaraj; Saravanan, Muthupandian (Frontiers in Molecular Biosciences, 2021)
Coronavirus disease (COVID-19) has emerged as a fast-paced epidemic in late 2019 which is disrupting life-saving immunization services. SARS-CoV-2 is a highly transmissible virus and an infectious disease that has caused fear among people across the world. The worldwide emergence and rapid expansion of SARS-CoV-2 emphasizes the need for exploring innovative therapeutic approaches to combat SARS-CoV-2. The efficacy of some antiviral drugs such as remdesivir, favipiravir, umifenovir, etc., are still tested against SARS-CoV-2. Additionally, there is a large global effort to develop vaccines for the protection against COVID-19. Because vaccines seem the best solution to control the pandemic but time is required for its development, pre-clinical/clinical trials, approval from FDA and scale-up. The nano-based approach is another promising approach to combat COVID-19 owing to unique physicochemical properties of nanomaterials. Peptide based vaccines emerged as promising vaccine candidates for SARS-CoV-2. The study emphasizes the current therapeutic approaches against SARS-CoV-2 and some of the potential candidates for SARS-CoV-2 treatment which are still under clinical studies for their effectiveness against SARS-CoV-2. Overall, it is of high importance to mention that clinical trials are necessary for confirming promising drug candidates and effective vaccines and the safety profile of the new components must be evaluated before translation of in vitro studies for implementation in clinical use.